2020
DOI: 10.1590/s0102-053620200315
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic performance of arugula/nira intercropping in different cultivation arrangements

Abstract: Spatial planning of cultivation arrangements is essential to ensure the superiority of intercropping when compared with monocrop. Thus, the aim of this study was to evaluate the agronomic performance of arugula/nira intercropping in different cultivation arrangements. The experiment was carried out in a randomized block design, in a split plot scheme, the plots represented the cultivation arrangements and the subplots the production cycles (winter and spring). The arrangements were T1= arugula monoculture; T2=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
1
0
2
Order By: Relevance
“…Para a variável EiC (Figura 3C), observou-se um ajuste linear com aumento de 0,0002 μmol CO2 m -2 s -1 [µmol H2O mol -1 ar] -1 (T1) e 0,0004 μmol CO2 m -2 s -1 [µmol H2O mol -1 ar] -1 (T2) para cada incremento unitário da SN. Valores semelhantes aos observados no presente estudo para iWUE foram obtidos por Guimarães et al (2022) em estudos com a cultura da rúcula em consórcio com nirá, no qual os mesmos observaram valores entre 28,63 e 34,80 μmol CO2 m -2 s -1 [mol H2O m -2 s -1 ] -1 para EiC. Figura 3.…”
Section: Quadrado Médiounclassified
See 1 more Smart Citation
“…Para a variável EiC (Figura 3C), observou-se um ajuste linear com aumento de 0,0002 μmol CO2 m -2 s -1 [µmol H2O mol -1 ar] -1 (T1) e 0,0004 μmol CO2 m -2 s -1 [µmol H2O mol -1 ar] -1 (T2) para cada incremento unitário da SN. Valores semelhantes aos observados no presente estudo para iWUE foram obtidos por Guimarães et al (2022) em estudos com a cultura da rúcula em consórcio com nirá, no qual os mesmos observaram valores entre 28,63 e 34,80 μmol CO2 m -2 s -1 [mol H2O m -2 s -1 ] -1 para EiC. Figura 3.…”
Section: Quadrado Médiounclassified
“…Para que o reuso de efluentes seja de fato uma solução viável para a agricultura, estudos sobre os efeitos destes nas plantas são fundamentais para a viabilidade do seu uso, neste sentido, hortaliças como a cultura da rúcula (Euruca Sativa L.), alface (Lactuca sativa), entre outras, que são folhosas consumidas in natura, precisam ser avaliadas sob diversos critérios, principalmente no que diz respeito a absorção de nutrientes (Santos et al, 2022), trocas gasosas (Guimarães et al, 2022), crescimento e rendimentos (Oliveira et al, 2023;Dantas et al, 2019), para que se possa ter segurança alimentar e sanitária em relação a produção para fins comerciais.…”
Section: Introductionunclassified
“…Leafy vegetables stand out for their varied organoleptic and functional characteristics in the human body (FU et al, 2017). Brazil has a wide variety of leafy vegetables, produced predominantly in conventional systems; however, intercropping systems have been the subject of numerous studies and are demonstrated to be sustainable and profitable enhancers of land use efficiency when adopted by farmers (BARBOSA; MALDONADO JÚNIOR, 2015;NASCIMENTO;NASCIMENTO;CECÍLIO FILHO, 2018, GUIMARÃES et al, 2020. Collard greens, chicory and arugula are some of the main leafy vegetables produced in Brazil (ABSEM, 2016).…”
Section: Introductionmentioning
confidence: 99%